Kualitas Tidur dan Fungsi Kognitif pada Lansia - Dini Nur Alpiah; Firdausiyah Rizki Amallia; Nabilah Kurniati (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2022)
Sleep quality includes quantitative aspects such as sleep duration, sleep latency, as well as subjective aspects such as deep sleep and rest. Cognitive is an activity that involves and or requires activities to think, which functions to recognize or know about objects or situations or situations, which are associated with learning experiences and one's intelligence capacity. The purpose of this study was to determine the relationship between sleep quality and cognitive function in the elderly. The design of this study was cross-sectional, involving 100 elderly people. The measurement tools used are the Mini-Mental State Examination (MMSE) questionnaire and The Pittsburgh Sleep Quality Index (PSQI). The results showed that the proportion of severe sleep quality disturbance was 66% and light sleep quality was 34%. Statistical test results showed a p-value of less than 0.05. Furthermore, it was concluded that there is a relationship between sleep quality and cognitive function in the elderly.Keywords: elderly; sleep quality; cognitive function; Mental State Examination (MMSE); Pittsburgh Sleep Quality Index (PSQI) ABSTRAK Kualitas tidur mencangkup apek kuantitatif seperti durasi  tidur, latensi tidur, serta aspek subjektif seperti tidur dalam dan istirahat. Kognitif merupakan suatu aktivitas yang melibatkan dan atau memerlukan kegiatan untuk berfikir, yang berfungsi untuk mengenal atau mengetahui mengenai benda atau keadaan atau situasi, yang dikaitkan dengan pengalaman pembelajaran dan kapasitas inteligensi seseorang. Tujuan dari penelitian ini adalah untuk untuk mengetahui hubungan antara kualitas tidur dan fungsi kognitif pada lansia. Rancangan penelitian ini adalah cross-sectional, yang melibatkan 100 lansia. Alat ukur yang digunakan adalah kuesioner Mini-Mental State Examination (MMSE) dan The Pittsburgh Sleep Quality Index (PSQI). Hasil penelitian menunjukkan bahwa proporsi gangguan kualitas tidur berat adalah 66% dan kualitas tidur ringan adalah 34%. Hasil uji statistik menunjukkan nilai p kurang dari 0,05. Selanjutnya disimpulkan bahwa ada hubungan antara kualitas tidur dengan fungsi kognitif pada lansia.Kata kunci: lansia; kualitas tidur; fungsi kognitif; Mental State Examination (MMSE); Pittsburgh Sleep Quality Index (PSQI)